The Role of Digital Marketing in Sales Growth: Insights from an Internship at Arihant Commercial - Jain, Vardhman (ATLAS SkillTech University, 2025)
The title of the internship report is "AN INSIGHTFUL EXPLORATION: SALES AND BUSINESS DEVELOPMENT INTERNSHIP AT ARIHANT COMMERCIAL." It is an account of my experience as a Sales and Business Development Intern at Arihant Commercial, a company founded to offer innovative solutions in Interior & Exterior Design for Residential & Corporate Domains. This report provides a comprehensive overview of what I learned during my internship last summer, which was part of our 2nd-MBA Toolbox curriculum. The internship helped me understand the various tasks and products managed by individual employees and the organization as a whole. Throughout the internship, I was deeply involved in all aspects of the business development process, from weekday market identification to weekend client canvassing and customer relationship management. I also contributed to creating sales strategies and overseeing interior and exterior solutions, working closely with the installation team to ensure that high standards were maintained. Collaborating with a small, dynamic team allowed me to gain hands-on experience, and learning the delicate balance of craftsmanship and developing strong relationships with local subcontractors was crucial for delivering quality results. Under the guidance of my esteemed faculty mentor, Dr. Priya Harikumar, I was able to bridge the gap between theoretical concepts and their practical application in sales and business development across various industries. My apprenticeship year had a profound impact on my personal and professional development, and I felt compelled to share this practical experience in a dissertation about how modern enterprises require an entrepreneurial spirit. This executive summary serves as a preview of the detailed insights and learnings shared in the further sections of this report, illustrating why such an internship opportunity at Arihant Commercial is valuable.
Project Report on The Role of Digital Marketing in Sales Growth: Insights from an Internship at Arihant Commercial (2023-2025) Under the Guidance of Prof. Priya Harikumar
Keywords: Interior & Exterior Design; business development; market identification